The importance of the reconciliation agreement in the criminal process - Decailo, Petro; Chaplia, Ivanna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article is devoted to the study of the conciliation agreement in criminal proceedings. The article considers the provisions of the current criminal procedure legislation on the conclusion of a conciliation agreement. The significance of this agreement in criminal proceedings is highlighted and problems that arise in connection with its conclusion.                                                                                          With the entry into force of the new Criminal Procedure Code of Ukraine in 2012, there was an innovation provided by Ch. 35. This is a criminal proceeding based on a conciliation agreement. This implementation is due to the dehumanization and democratization of society. It provides for the resolution of a criminal conflict by concluding a conciliation agreement between the injured party and the suspect or accused, which does not pose a great public danger. The parties in this case independently decide on the conditions of release from criminal liability, sentencing, compensation. The introduction of this institute has led to many opinions among scientists about the negative or positive aspects of its activities. It is new to criminal justice, and the mechanism for implementing agreements needs some improvement, further research and more jurisprudence. Which makes the relevance of this study.  According to the Criminal Procedure Code of Ukraine, the main task of the criminal process is to protect the rights, freedoms, legitimate interests of the person involved in criminal proceedings. These provisions are implemented in connection with the reform and improvement of the rules of criminal procedure law of Ukraine, which are implemented in accordance with international human rights standards. This testifies to Ukraine's transition to European standards in criminal proceedings. Proceedings based on an agreement between the victim and the suspect or accused ensure the interests of individuals and also facilitate the speedy resolution of the case, without lengthy pre-trial and trial proceedings.